2021
DOI: 10.1111/ijcp.14289
|View full text |Cite
|
Sign up to set email alerts
|

Womens' self‐management skills for prevention and treatment of recurring urinary tract infection

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
(52 reference statements)
0
15
1
Order By: Relevance
“…[17] In East Africa, high community prevalence of UTIs, combined with high levels of AB self-medication, may further exacerbate ABR, [14] particularly considering self-management for UTI symptoms is extremely common. [18,19]…”
Section: Introductionmentioning
confidence: 99%
“…[17] In East Africa, high community prevalence of UTIs, combined with high levels of AB self-medication, may further exacerbate ABR, [14] particularly considering self-management for UTI symptoms is extremely common. [18,19]…”
Section: Introductionmentioning
confidence: 99%
“…These perspectives could be relevant since at least 10% of the GPs reported they would prescribe antibiotics at patients’ request. Moreover, patients who have experience with UTIs could have multiple motivations for requesting urine tests, such as fear of a complicated UTI [ 33 , 34 ]. With regard to antibiotic stewardship, it could also be interesting to focus more on non-antibiotic alternatives to treat symptomatic UTIs [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, most women with a history of cystitis in our study had gained information as a result of their experience with cystitis, which was also found in previously performed qualitative studies. The results of these studies showed a large variation in patient knowledge about UTIs and prophylactic strategies for recurring UTIs [ 30 , 32 ]. Especially women in our study who had experienced pyelonephritis or other complicated UTIs indicated that they were afraid to develop this again when they had cystitis.…”
Section: Discussionmentioning
confidence: 99%